Conceptual framework for Islamic social financing and financial sustainability in Malaysian Higher Education Institutions (HEIS) / Mohd Azrin Abd Rahim, Muhammad Nazmul Hoque and Abul Bashar Bhuiyan - Abd Rahim, Mohd Azrin; Hoque, Muhammad Nazmul; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This paper aims to explore the empirical review and develop a conceptual framework based on possible available options of social financing for higher education, especially the role of financial institutions and religious motivation towards social financing and financial sustainability in Malaysian higher education. The study used available resources of empirical articles from available online data-based. The study summarized the empirical review findings that there are significant contributions of Islamic social financing for ensuring higher education sustainability in the Muslim Society in Malaysia. Especially, zakat, sadaqat and waqf, qard, and kafala and other modern forms of Islamic financial services such as Islamic microfinance, Sukuk, and takaful play a significant role in education sustainability in the Muslim Society all over the world. Moreover, the study will use the above empirical review findings and develop a conceptual framework for ensuring higher education institutes' financial sustainability in Malaysia. The present study will justify drawing necessary policy guidelines and manuals for action projects to implement the above model in Malaysia and the regions.